'Development through connectivity': India's maritime narrative. Issue 3 (2nd September 2019) - Rao, P. V.
ABSTRACT: Motivated by regional economic integration and geo-strategic interests, the Bay of Bengal (BOB) littorals are now striving to build land and maritime connectivities to promote trade and investment networks. India's geographic centrality to the BOB region makes it indispensable to any regional connectivity plan. Indeed, regional groups such as SAARC and BIMSTEC also encouraged its members to devise regional plans to build transport infrastructure; however, no enthusiasm was exhibited to create such linkages until recently when extraregional initiatives primarily by China began transforming the economic and geopolitical profile of the region as it pushed for transportation links with the BOB countries. Beginnings with Burma, China moved ahead constructing a chain of infrastructure projects in Sri Lanka, Bangladesh and Thailand. Against this backdrop, this paper argues that more the extraregional initiatives than intraregional efforts have driven the BOB states to promote intraregional connectivities.